2017
DOI: 10.1530/rep-16-0484
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-sensitive lipase deficiency alters gene expression and cholesterol content of mouse testis

Abstract: Hormone-sensitive lipase-knockout (HSL−/−) mice exhibit azoospermia for unclear reasons. To explore the basis of sterility, we performed the following three experiments. First, HSL protein distribution in the testis was determined. Next, transcriptome analyses were performed on the testes of three experimental groups. Finally, the fatty acid and cholesterol levels in the testes with three different genotypes studied were determined. We found that the HSL protein was present from spermatocyte cells to mature sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 54 publications
0
22
1
Order By: Relevance
“…Several studies have reported that the expression of proteins involved in lipid metabolism can affect testicular function in mice (Wang et al, 2017;Sharma et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the expression of proteins involved in lipid metabolism can affect testicular function in mice (Wang et al, 2017;Sharma et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Obese, diabetic and aging women typically suffer from abnormal body metabolism such as hypertension, hyperglycemia and hyperlipidemia [11][12][13][14][15][16], causing long-term stress in oocytes [17], which severely damages the quality of oocytes, thereby leading to lower pregnancy rate [18].…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol is the most abundant sterol of membrane properties in sperm cells that have the capacity to inhibit the capacitation [53]. It was reported that spermiogenesis ceased at the elongation phase of HSL-knockout mice [54]. Thus, higher abundance of HSL in ram spermatozoa probably represents higher capacity ability.…”
Section: Differences In Spermatozoa Proteins Between Ram and Buckmentioning
confidence: 99%